Cobalt‐based coordination polymer as high activity electrocatalyst for oxygen reduction reaction: Catalysis by novel active site CoO4N2. (12th December 2019) - Chen, Xin; Ge, Fan; Lai, Nanjun
Summary: [{Co3 (μ3 ‐OH)(BTB)2 (BPE)2 }{Co0.5 N(C5 H5 )}] (Co‐CP) as a coordination polymer for catalyzing oxygen reduction reaction (ORR) has recently been reported to exhibit high ORR performance because of its novel structural characteristics. Nevertheless, the detailed mechanism remains far from enough. Herein, first‐principles study of the ORR process of Co(C6 H5 CO2 )2 (C5 H5 N)2 is carried out, which is the constructed model of monomeric unit for this compound. Most interestingly, the calculated results uncover that in the second proton transfer step, the active site contributes to the reaction is not only the Co atom, but also the O and N atoms which are directly bonded to the Co atom that construct a novel active site CoO4 N2 . Further analysis of the electronic structure demonstrates that the Co, O, and N atoms in the CoO4 N2 local structure have participated the electron transfer during the entire ORR process. By analyzing the relative energy changes of whole reaction, it can find that the favorable ORR pathway on the Co(C6 H5 CO2 )2 (C5 H5 N)2 is the 4e − pathway, and the overpotential of ORR on Co(C6 H5 CO2 )2 (C5 H5 N)2 is calculated as 0.43 V, which is consistent with experimental observation and lower than that on the Pt(111). Furthermore, the results of first‐principles molecular dynamics simulations and density of states (DOS) show that Co(C6 H5 CO2 )2 (C5 H5 N)2 presents good stability. And it also possesses high anti‐poisoning ability to some impurity gases such as CO, NO, and NH3 . Abstract : The ORR activity of a new coordination polymer [{Co3 (μ3 ‐OH)(BTB)2 (BPE)2 }{Co0.5 N(C5 H5 )}] is investigated by DFT. This coordination polymer possess novel active site CoO4 N2 to catalyze ORR. This new coordination polymer exhibits excellent catalytic activity, stability and anti‐poisoning ability.